Foundational disputes on the education and the citizenship of women. Considerations on the Argentine case (Praxis Educativa, 2012)
This paper analyzes, from a gender point of view, the relationship between education, women citizenship in two foundational moments of Argentinean educational system: 1894-1994. It focusing in the theorics and politics feminist’s genealogies at the time of the bourgeois’s revolutions the education was thought like a mainstream for political change, namely it was crucial to debate about whom and haw must to be educated. The debate took place in the Argentinean case in the end of 19th Century, and the result was the 1420 Law. But a century of the educational practices were fading the traces of political polemics and putting in the scene pedagogic and technical issues. A new discussion about education, politics, and women citizenship take place in the ’80 with the return of democracy. At the same time a deep transformation of social structure occurred. The discussion culminated with the 24195 Law, in 1994. It took place in a singular crossroad: the return of citizenship question, changes in the social structure (the so called news inequities), a sensibility about differences (sexual, racial, cultural differences).In this situation the debate about women education like a citizens was crossed by a deep tensions.
Keywords: education; past and present; citizenship of women; foundational disputes